2021
DOI: 10.1088/1757-899x/1064/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

New nitriding process of high-alloyed maraging steel for cryogenic operation

Abstract: The paper considers the gas nitriding process with cyclic alternation of atmospheres: ammonia and an ammonia mixture with air for strengthening the corrosion-resistant high-alloyed steel 03Cr11Ni10Mo2Ti, designed to operate at cryogenic temperatures. The formation in steel of a nitrided layer of 130—150μm thickness with increased microhardness (more than 12GPa) is shown experimentally. During the final stage in the ammonia and air environment, iron oxides remain in the compound zone, and a sharp drop in hardne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Интенсификация азотирования достигается также применением многокомпонентных атмосфер, в том числе, путем термо-и газоциклирования [9 -11]. Так, циклические процессы с чередующейся подачей аммиака и воздуха не уступают процессам ионно-плазменного азотирования по скорости формирования азотированного слоя, создают дополнительные возможности регулирования фазового состава слоя и получения заданных свойств как в углеродистых, так и в легированных сталях [12,13].…”
Section: наукоёмкие технологии электро-физикохимической и комбинирова...unclassified
“…Интенсификация азотирования достигается также применением многокомпонентных атмосфер, в том числе, путем термо-и газоциклирования [9 -11]. Так, циклические процессы с чередующейся подачей аммиака и воздуха не уступают процессам ионно-плазменного азотирования по скорости формирования азотированного слоя, создают дополнительные возможности регулирования фазового состава слоя и получения заданных свойств как в углеродистых, так и в легированных сталях [12,13].…”
Section: наукоёмкие технологии электро-физикохимической и комбинирова...unclassified
“…Another way for nitriding acceleration consists in application of staged or cyclic processes with changing of nitriding potential. It was shown that cyclic processes in changing ammonia-air atmospheres provide specific opportunities for phase composition regulation and for achievement of given properties of nitrided surface [5,6].…”
Section: Introductionmentioning
confidence: 99%